The Implementation of the Defense Industrial Base (DIB) a Comparative Study of Indonesia and Brazil - Budhi Achmadi; Soesilo Zauhar; Bambang SH; Andy Fefta W (Wacana Journal of Social and Humanity Studies, 2019)
Policy implementation holds an important position in the public policy cycle, as it determines the success or failure of policies formulated. The defense industrial base is one of the important public policies in many countries because it can play a multi-faceted role function, among which are as a politico-diplomatic status, an economic driver, and a centrifugal force for growth. However, as a public policy, the outputs and outcomes of DIB policy implementation are determined by, among others, key policy issues, policy formation processes, and policy directions or objectives. These variables are influenced by the leadership style and then determine the impact of policies.Â Keyword: Policy implementation, Public policy, The Defense Industrial Base